Os modos de fazer dos diretores de escolas públicas paulista frente as exigências da Secretaria da Educação - Fovali, Fernanda Santoni (2020)
In this research, I propose to analyze the performance of principals in the public education system in the state of São Paulo in order to meet the requirements of the Department of Education. Throughout this study, some concerns that motivated and directed the research have emerged. What demands are imposed on the principals by the Department of Education? How are these demands evaluated by the principals based on their reality? What is the understanding of the investigated principals regarding their working context? What do principals do in their daily routings to meet the school’s requirements? What profile does the Department of Education demand from this principal regarding his/her daily life routine and practice? With these inquiries a general objective was identified to verify the techniques are created and used by the principals in order to deal with the demands and requirements of the SEDUC-SP and the school’s routine. The specific objectives of this study are the following: (1) Analyze to which extent these public school principals go to meet the SEDUC-SP requirements; (2) Identify how these principals circumvent the demands to meet the workplace demands; (3) Be aware of what adjustments are made by the principals to meet the demands in an egalitarian and differentiated manner. Not only that but also to prioritize the SEDUC-SP requirements regarding all types of management upon resolutions and daily school routine and ; (4) Highlight how principals understand the contribution of the documents in the school’s day to day life and the workplace. Based on the objectives presented, the research was then developed according to a qualitative approach, through the realization of document analysis and bibliographic survey. A focus group was used for data- collection. The Department of Education primary source documents, books and publications suggested in resolution SE 56 from October 14, 2016, São Paulo’s guidelines’ policies were defined as the objective of this study, as well as publications from the exclusive network for principals which regulates the profile and management of schools belonging to the SEDUC-SP. The studied subjects were four school principals from Paulista city in the state of São Paulo. Literature authors that will be analyzed are such, Lück (2009) to discuss the dimensions of school management; Piolli (2015, 2016, 2019), Afonso (2007), Barroso (2005), Ball (2012), Teodoro (2011), Maués (2011) and Russo (2009) for public policies and the work context of the directors reference; Certeau (1998) for focus group analysis. The results obtained in the investigation highlight that the school principals work to meet daily demands, often creating their own tactics to meet the requirements established by the Department of Education.